How Songs Get on the Radio, or What does Rihanna's Chart Success Mean for the Researcher of Innovations - Elena Melnikova (Journal of Economic Sociology, 2016)
The review discusses Gabriel Rossman's monograph Climbing the Charts: What Radio Airplay Tells Us about the Diffusion of Innovation. The author analyzes how songs get on the radio. Describing this process in terms of diffusion of innovations theory, Rossman focuses on how innovations get adopted rather than who adopts innovations. He draws on the “gatekeeping model” of Paul Hirsch, who advocates a production of culture approach that sees popular culture as a flow process where cultural objects, including songs, move from the artists through cultural distributors and surrogate consumers to the ultimate consumers. Rossman concentrates on one element of this flow process — a channel from distributors (record labels) to surrogate consumers (radio stations). The result of his analysis is a detailed picture of the radio industry which shows us two main external forces driving airplay. The first one is corruption in music industry. The second force is a system of music genre classifications which regulates the process of evaluation of new songs by programming directors of the radio stations. Rossman’s findings are based on rich quantitative and qualitative data, first of all, on the cumulative airplay of more than a thousand randomly selected singles released between 2002 and 2007.